2016
DOI: 10.1209/0295-5075/116/56001
|View full text |Cite
|
Sign up to set email alerts
|

The true structural periodicities and superspace group descriptions of the prototypical incommensurate composite materials: Alkane/urea inclusion compounds

Abstract: The prototypical family of incommensurate composite materials are the n-alkane/urea inclusion compounds, in which n-alkane guest molecules are arranged in a periodic manner along one-dimensional tunnels in a urea host structure, with an incommensurate relationship between the periodicities of the host and guest substructures along the tunnel. We develop interpretations of the structural periodicities, superspace group descriptions and symmetry properties of the lowtemperature phases of n-alkane/urea inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(35 citation statements)
references
References 61 publications
7
28
0
Order By: Relevance
“…At the same time, the main reflections of the host substructure ( h , k , l′ , 0) with h + k odd and the main reflections of the guest substructure ( h , k , 0, m′ ) with h + k odd are very weak, but it is evident [ 28 , fig. 3b] that their intensities increase as temperature decreases, which is the predicted behaviour for ( Q 2 ) 2 according to our model ( figure 5 b ) and is in good agreement with experimental observations that we reported recently [ 31 ]. Below 130 K, the intensities of these reflections exhibit a marked and progressive increase [ 28 , fig.…”
Section: Comparison With Experimental Datasupporting
confidence: 93%
See 3 more Smart Citations
“…At the same time, the main reflections of the host substructure ( h , k , l′ , 0) with h + k odd and the main reflections of the guest substructure ( h , k , 0, m′ ) with h + k odd are very weak, but it is evident [ 28 , fig. 3b] that their intensities increase as temperature decreases, which is the predicted behaviour for ( Q 2 ) 2 according to our model ( figure 5 b ) and is in good agreement with experimental observations that we reported recently [ 31 ]. Below 130 K, the intensities of these reflections exhibit a marked and progressive increase [ 28 , fig.…”
Section: Comparison With Experimental Datasupporting
confidence: 93%
“…Finally, in the context of the (3 + 1)-dimensional description of the superspace group in phase II of n -nonadecane/urea, the fact that satellite reflections are indexed with large values of l′ and m′ [ 31 ] may appear unusual. However, we note that examples of incommensurate systems with high values of indices for satellite reflections arise when the modulation function becomes discontinuous and a non-analytical ‘soliton regime’ can exist [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of using these careful measurements, M. Couzi et al . used the results from their recently published article, which describes an X-ray diffraction study performed on n -nonadecane-h 40 /urea-h 4 but with measurements reported at only two temperatures (147 K and 100 K) [11]. In a Comment concerning that article [2], which they did not contest, we demonstrated that their data have no relevance.…”
mentioning
confidence: 86%